A hybrid vegetation detection framework: Integrating vegetation indices and convolutional neural network - Sumayyah Dzulkifly (Tanjong Malim, 2021)
A hybrid vegetation detection framework: Integrating vegetation indices and convolutional neural network by Sumayyah Dzulkifly